301 Blood Grouping and Save in Day Case Laparoscopic Surgery – Potential for Resource Savings?. (28th February 2022) - Ramasamy, S.; Kumar, S.; Al-Habsi, R.; GS, D.; Keeler, B.; Khanna, A.
Abstract: Introduction: Currently, patients listed for Laparoscopic cholecystectomy and Laparoscopic Appendicectomy undergo routine Blood Grouping and Saving (G&S) pre-operatively. Blood transfusion administration in this context is a rare occurrence. Processing of G&S samples takes approximately 45 minutes and costs £31 per sample. This excludes the phlebotomy and junior doctor resources for sample collection, which incurs additional costs. We retrospectively assessed the blood transfusion requirements in those patients who underwent either a laparoscopic appendicectomy or cholecystectomy in the last 18 months at a busy District General Hospital (Milton Keynes Hospital) to determine if there were any potential costs and resource savings that could have been made. Method: Retrospective case notes analysis of patients who had laparoscopic cholecystectomy and laparoscopic appendicectomy from January 2019 to June 2020 focusing on timing of G&S, preoperative and postoperative haemoglobin, the timing of blood transfusion and the number of units transfused. Results: Of a total of 613 patients, 323 patients had laparoscopic cholecystectomy. 256 (78.8%) of these had 1 G&S sample and 96 (29.7%) had 2 samples. 290 patients had laparoscopic appendicectomy. 190 (65.5%) of these laparoscopic appendicectomy patients had 1 G&S sample and 89 (30.6%) had two G&S samples. None of the 613 patients was transfused. The total cost of G&S was £22, 196. Conclusions: Our study illustrates that in this group there was no requirement for blood transfusion. Routine group and save samples result in a significant waste of resources and finances. Targeted groups and save samples should be reserved for high-risk groups only.